10=3(x-1)-(x-9)

Simple and best practice solution for 10=3(x-1)-(x-9) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10=3(x-1)-(x-9) equation:



10=3(x-1)-(x-9)
We move all terms to the left:
10-(3(x-1)-(x-9))=0
We calculate terms in parentheses: -(3(x-1)-(x-9)), so:
3(x-1)-(x-9)
We multiply parentheses
3x-(x-9)-3
We get rid of parentheses
3x-x+9-3
We add all the numbers together, and all the variables
2x+6
Back to the equation:
-(2x+6)
We get rid of parentheses
-2x-6+10=0
We add all the numbers together, and all the variables
-2x+4=0
We move all terms containing x to the left, all other terms to the right
-2x=-4
x=-4/-2
x=+2

See similar equations:

| 12/100=2/x | | 2h+138=1,040 | | 138+2h=1,040 | | 138+2h=1.040 | | 4x-4=9x+17 | | -7(5-3n)=-140 | | 1/2x+2/3x+12=18 | | 23229=34x/1-(1+34)^-34 | | 7(d-5)=12=15 | | 36=4×r | | -3(1-7n)=123 | | Z+4-6=10-2z | | 4+-n=-15 | | 8m=172 | | 16^(-x+44)=128 | | 174=48n+18 | | 3(7k^2+5k-2)=0 | | 3(7k+5k-2)=0 | | 7x-5=212 | | 7(n+8)-n=86 | | 13x+50=9x+100 | | 8z=11 | | 5h−7=1+h | | 3(7k^2+5k-6)=0 | | 7x+3x+11+39=180 | | 3(3-3x)=2(X+3)+30 | | 3(7k+5k-6)=0 | | C^2-13^c+42=0 | | $14.95+a=$7.55 | | 7x+3x+11=39 | | 4x+7=9x-18 | | 8(u-2=64 |

Equations solver categories